DSP improvement of a vector speed induction motor control with a RST and adaptive fuzzy controller - Mihoub Youcef; Toumi Djilali; Sandrine Moreau; Hassaine Said; Daoud Bachir (Bulletin of Electrical Engineering and Informatics, 2021)
The aim of this work is to improve the dynamics and to overcome the limitation of conventional fixed parameters PI controller used in induction motor (IM) field-oriented control (FOC). This study presents and implements a RST and an adaptive fuzzy controller (AFC) to enhance variable speed control. Theoretical background of theses controllers is outlined and then experimental results are presented. Practical implementation has been realized on a board with a 1.1 KW IM supplied by 10 KHz space vector pulse width modulation current regulated inverter used as power amplifier consisted of 300V, 10A IGBT and Matlab/Simulink environment. Test benches have been established under different operating conditions in order to evaluate and compare the performances of the PI, IP, and polynomial RST and adaptive fuzzy controllers. Parameter variations for the rotor and the inertia moment variation were done in order to compare and verify the robustness of each controller. High dynamic performances and robustness against parameters variation were obtained with the use of both RST and AFC.